(untitled) (Confluenţe Bibliologice, 2017)
The article describes the activities dedicated to National Awareness Week on Libraries and Librarian’s Day in Republic of Moldova. This year, the National Awareness Week on Libraries "Your Library - Your Progress" was celebrated on May 3rd. On this day, the activities started on April 23 of the Librarian’s Day in the Republic of Moldova have been concluded. This activity is an important objective of ERASMUS+ Capacity Building in Higher Education LNSS Project "Library Network Support Services: Modernizing Libraries in Armenia, Moldova and Belarus through Library Staff Development and Reforming Library Services". The program was a complex one, and included various forms of promoting libraries, books, reading, electronic resources: conferences, Flash Mobs, book presentations, Cosplay, exhibitions, seminars, public debates, tribute sessions of librarians.